Hubungan Skor Penyakit Tungro terhadap Kehilangan Komponen Hasil Padi - Firmansyah Firmansyah; Khaerana Khaerana; Effi Alfiani Sidik (Universitas Bangka Belitung, 2023)
The Tungro disease is a significant issue that impedes rice production. It is spread by green leafhopper vectors carrying the RTBV and RTSV pathogens. The infection causes a decline in various components of rice yield and is categorized based on a scoring system ranging from 1 to 9. The objective of this study was to investigate the correlation between the scoring values and yield loss, as well as determine the production factor that had the greatest impact on yield loss for each score. The research was conducted at the IP2TP Tungro Disease Research Station between August and October 2020. A purposive sampling technique, which involved the direct observation of tungro-affected rice fields, was employed as the research method. A score was assigned to 5 clumps of plants for each case. Data analysis was performed using simple regression, correlation, and PCA. The findings indicate that with the exception of the empty grain parameter, which increased along with the scoring value, each increment in the Tungro score resulted in a decrease in the yield variables. The components of yield that declined in all scores as a result of Tungro infection included total grain weight, weight of 100 seeds, total grain count, and total grain content.